Ameliorative effects of Musa sapientum peel extract on acetic acid-induced colitis in rats (2016)
Ameliorative effects of Musa sapientum peel extract (MSPE) were studied on Acetic Acid (AA)-induced colitis in rats. From a dose response study, the effective and yet, safe for the treatment of AA-induced colitis in rats was determined, and also, a further study was carried out to determine the effective fraction(s) of MSPE that will be useful in the treatment of AA induced colitis in rats. Colitis was induced with 0.2 ml of 6% acetic acid through a lower abdominal laparotomy. Treatment with graded doses of methanolic extract of dried peel of Musa sapientum (MS) (50, 100 and 200 mg/kg) for 7 days in AA induced colitis in rats showed 50 mg/kg as an optimal effective dose for the healing of AA induced colitis in rats. This dose (50 mg/kg) was further studied with fractions of MSPE in comparison to a standard drug (sulfasalazine) of the same dose (50 mg/kg) on AA induced colitis in rats for 18 days. Colitis was assessed using stool consistency, macroscopic gross score and histological studies. Normal stool consistency was seen early in treated animals as compared with control; MS peel (crude extracts and fractions) significantly reduced macroscopic and histologic colon tissue damage in a manner similar to that of sulfasalazine. The results from these findings suggests that MSPE fractions of ethyl acetate and methanol may be effective in reducing both macroscopic and histological damage in a manner similar to sulfasalazine, and that it may be helpful in the treatment of colitis